Pengembangan Kampoeng Wisata Cinangneng Berdasarkan Tipologi Wisatawan - Syawaliyah Ulfah (Fakultas Pariwisata Universitas Pancasila, 2018)
Bogor Regency of West Java Province that is developing the potential of its territory for tourist destination and attract the attention of local and foreign tourists to visit. The location that researcher has been choosed to do research is Kampoeng Wisata Cinangneng which is located in Bogor regency. Kampoeng Wisata Cinangneng located in the village of Cihideung Udik, Ciampea District has a tourism concept based on nature tourism and educational tourism. The purpose of this research are to identify the development component of the destination (factual conditions in the field), identify the tourist tipology who visit Kampoeng Wisata Cinangneng and develop strategies Kampoeng Tourism Development Cinangneng based on tourist tipology. This research is a descriptive quantitative and descriptive qualitative research. Quantitative research is conducted to determine the tourist characteristics and tourist tipology that calculated by used percentages. Qualitative research is conducted to find out the development strategy in Kampoeng Wisata Cinangneng. Generally qualitative research method is intended for research that is observed case. The collected data will be analyzed using SWOT analysis, followed by compiling alternative strategies using SWOT matrix. Kampoeng Wisata Cinangneng has a good enough strength to be developed based on the tourist tipology, but the nature and culture of the existing tourism has not been maximally utilized, although it has a good accessibility, less complete amenitas, condition of supporting facilities is complete enough. The result of typology is that tourists who visit Kampoeng Wisata Cinangneng tend to mid-centric tipology. Based on the results of SWOT analysis bring out an alternative strategy that is: Invite local people to teach tourists to make souvenirs that them make, adding outbound packages to be variants that can be offered to tourists, make a places to eat in the middle of rice field with food from local community.